Changes in psychosocial adjustment of adolescents when applying the physical education lessons - Klizas, Šarūnas; Malinauskas, Romualdas; Žvirdauskas, Dainius (Pedagogika, 2014)
The aim of the present study was to establish the changes in psychosocial adjustment of adolescents conducting modified lessons of physical education. The educational experiment was carried out in one Kaunas secondary school. The research was performed in several stages. First, the experimental (n = 185) and the control (n = 192) groups were selected. Then the groups underwent the primary assessment of adolescents’ psychosocial adjustment. Afterwards, the experimental impact (the program of enhancing adolescents’ psychosocial adjustment in the lessons of physical education) was applied on the experimental group and, after concluding the experiment, the experimental and the control groups underwent the concluding testing. 377 students in total took part in the experiment. Classes of EG during the schooling year had modified lessons of physical education twice a week. During the course, they had a theoretical lesson once a month. In the theoretical lessons, students were introduced to the disturbances of adolescent interrelations and methods of their elimination in the process of intense physical activity. During practical lessons, sportive games increasing physical qualities were applied to EG (basketball, volleyball, football) according to the general programs of physical education of Lithuania (2009); besides, Pilates exercises and imitational games strengthening psychosocial adjustment based on role-taking were also applied. CG forms also had two weekly lessons of physical education with the same teacher, the author of the research, but the lessons were not modified and they proceeded according to the General programs of the subject of physical education (General Curriculum of Primary and Basic Education, 2009). For the estimation of the level of adolescents’ psychosocial adjustment, a modified questionnaire by C. Rogers and R. Dymond was applied. Besides the main indices of adolescents’ psychosocial adjustment the questionnaire included other subscales (evaluation of others, emotional comfort, integrity,) which helped reveal psychosocial adaptation of a personality, in order to discover the level of communication skills of the students of middle schooling age, a questionnaire by Miškinis was employed. The repeated research performed after the program of the strengthening of psychosocial adjustment in the lessons of physical education showed that the results of emotional comfort of EG statistically significantly altered; after the educational experiment they showed (62.02 ± 10.33 points) (t = – 3.35; p = 0.001) in comparison with EG results before the educational experiment (58.64 ± 9.02 points). When analyzing the scale of communication we have to observe that EG and CG results before the experiment were similar. It was established that before the experiment, the results of EG (2.01 ± 0.4 points) and CG (1.94 ± 0.3 points) were not statistically significantly different (t = 1.91; p > 0.05). The repeated research applied after the program of strengthening of psychosocial adaptation during the lessons of physical education showed that the results of EG altered statistically significantly after the educational experiment (2.28 ± 0.5 points) (t = –6.30; p = 0.001) in comparison to EG results before the educational experiment (2.01 ± 0.4 points). This means that after the educational experiment, EG students of middle schooling age might communicate easily. It was established that the program of educational devices designed for the improvement of psychosocial adaptation during the lessons of physical education needs to be developed on the grounds of the social learning theory, social cognition theoretical attitude, liberal education paradigm and cognitive theory by applying the rational combinations of: development of positive attitudes towards oneself, social support, problem situation, emotional support, correspondence activities, performance games, operative games, Pilates excercises. It was established that the properly construed and purposefully applied complex of the devices of educational impact during the lessons of physical education influences the psychosocial adaptation of the adolescents: after the experiment in the experiment group, integrity (p = 0.002), emotional comfort (p = 0.001) and the level of communication (p = 0.001) increased statistically significantly.